The great ideas of philosophy - Robinson, Daniel N.; Aigret, Jaimée M.; Leven,Jon; Dooley,Tom; Teaching Company (Chantilly, Virginia The Teaching Company, 1997)
Sixty lectures by Daniel N. Robinson tracing the abiding issues of philosophy across the centurie.
pt. 5. disc 9. Alan Turing in the forest of wisdom -- Four theories of the good life -- Ontology, what there "really" is -- Philosophy of science, the last word? -- Philosophy of psychology and related confusions -- Philosophy of mind, if there is one -- disc 10. What makes a problem "moral" -- Medicine and the values of life -- On the nature of law -- Justice and just wars -- Aesthetics, beauty without observers -- God, really?
Lecture transcript and course guidebook published to accompany DVD and and videotapes with the same title.
Includes bibliographical references and index.
Keywords: Herodotus; Socrates; Hippocrates; Philosophy -- History; Philosophy -- Study and teaching (Higher)